Effects of phosphate and citric acid on Pb adsorption by red soil colloids. Issue 4 (14th January 2016) - Zuo, Jichao; Fu, Qingling; Su, Xiaojuan; Liu, Yonghong; Zhu, Jun; Hu, Hongqing; Deng, Youjun
Abstract : There are abundant organic acids in rhizospheric soil, which may interfere in the reaction between phosphate and heavy metals. Effects of phosphate on Pb 2+ adsorption by red soil colloids(Ultisol) were studied in the presence of citric acid (Cit) through batch equilibrium experiments, Zeta potential and X‐ray diffraction (XRD) analyses. Results showed that in the presence of different concentrations of phosphate (P), the peak‐like curves of Pb 2+ sorption was moved up even disappeared. When the Langmuir equation was used to model isothermal adsorption curve of Pb 2+, the adsorption reaction constant (K), the maximum adsorption quantity (Xm ) of several treatments were both in a decreasing order of 1.0 mmol/L P > 1.0 mmol/L P + 0.5 mmol/L Cit > 0.5 mmol/L Cit. Under the influence of citric acid, the Pb 2+ adsorption amount increased at pH < 4.5, and then decreased gradually with pH increase. The order of Zeta potential reduction was: 1 mmol/L P + 0.5 mmol/L Cit > 0.5 mmol/L Cit > 1 mmol/L P, which were different from that of the Pb 2+ adsorption amount, suggesting that the adsorption of Pb 2+ was not only an electrical adsorption in the presence of P. XRD patterns proved that occurrence of pyromorphite for the treatment with 1.0 mmol/L P addition, whereas no lead phosphate peak was detected in other treatments. The mechanism of Pb 2+ adsorbed in red soil colloids with addition of phosphate was primary formation of pyromorphite‐like compounds. However, 0.5 mmol/L Cit inhibited the formation of pyromorphite. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 969–974, 2016